The Point of a Ban: Or, How to Think about Stem Cell Research - Meilaender, Gilbert (The Hastings Center report, 2001)
We might be convinced that the goal of relieving suffering offers a straightforward justification of sacrificing embryos in research. Or we might hold that although embryos merit our respect, the greater the good to be achieved by destroying them, the more respect must give way to research. Or, if we take the notion of respect seriously, we might find that relieving suffering is a real but not supreme imperative.